THE CAUSAL MODEL FACTORS AFFECTING ETHIC MANAGEMENT OF SECONDARY SCHOOL ADMINISTRATORS IN THE EASTERN REGION, UNDER THE BASIC EDUCATION COMMISSION - Yamlamoon, Bunjaporn; Pruettikul, Sataporn; Anannawee, Paradee (Journal of Educational Review Faculty of Education in MCU, 2020)
This research articles was to study the causal model factors affecting ethic management of secondary school administrators in the Eastern Region, under the Basic Education Commission. The research consisted of 2 main steps: Step 1) Studied of causal model factors affecting ethic management of secondary school administrators, under the Basic Education Commission by document reviewed and interviewed 16 administrators. Step 2) Examining the causal model and empirical data by analyzing confirmation components and hypothesis model. The sample were 640 teachers. Data analyzed by , SD, CFA and SEM (Structural Equation Modeling) by computer package program. The findings of the research. 1) Ethic management of secondary school administrators in the Eastern Region, under the Basic Education Commission was at high level. 2) The factors affecting ethic management of secondary school administrators in the Eastern Region, under the Basic Education Commission overall were at high level. 3) Confirmatory Factor Analysis: (CFA) of the factors model of ethic management of secondary school administrators in the Eastern Region, under the Basic Education Commission, vision factor, policy clarity factor, politics in organization factor, good governance administration factor, leader traits factor, and community/ social factor. There were consistent with empirical data. 4) The causal model factors affecting ethic management of secondary school administrators in the Eastern Region, under the Basic Education Commission was consistent with the empirical data, (x2=653.79, df=272, x2/df=2.40, GFI=0.93, CFI=0.91, AGFI=0.90, SRMR=0.05, RMSEA= 0.047) Moreover, the policy clarity factor, community social factor, and politics in organization factor were directed and indirected effecting Ethic management of secondary school administrators. (p<.05)